Reproductive success of Fernseea itatiaiae in the community context of plant-pollinator interactions - Mendonça Rigotto, Sarah; Bergamo, Pedro Joaquim [UNESP]; Alves Siqueira, Ricardo; Wolowski, Marina (Springer Nature, 2025)
Network analysis is a powerful tool to identify key species for the stability of ecological communities. For endangered species like Fernseea itatiaiae, understanding its role within the network is vital for revealing how interactions with pollinators influence its reproductive success and vulnerability. This insight is crucial for conservation strategies. Thus, the community context revealed by interaction networks can inform conservation strategies for threatened species. The ornithophilous bromeliad Fernseea itatiaiae (Wawra) Baker is restricted to the Itatiaia Plateau (southeast Brazil) and is assessed as endangered (EN). Fernseea itatiaiae and 14 other plant species have floral morphology related to hummingbird pollination (ornithophily), serving as floral resources for hummingbirds in the area. We used a field monitoring experiment to assess how the phenology and availability of conspecific and heterospecific ornithophilous floral resources at the community level affect the pollination of F. itatiaiae. We measured the fruit set, seed production (from controlled pollination experiments) and total amount of pollen deposited on stigmas as proxies of F. itatiaiae reproductive success and related it to the community context (monthly abundance of conspecific and ornithophilous flowers, floral display, presence of ornithophilous neighbors). The results showed overlapping flowering peaks of some ornithophilous plant species (Buddleja speciosissima and Gaultheria serrata) with F. itatiaiae. The species with the strongest interactions with shared hummingbirds were Fuchsia regia, F. itatiaiae, and Buddleja speciosissima, based on the relative frequency of hummingbird visitation per hour. Additionally, we found that, although the floral community context had no direct significant influence on the pollination success of F. itatiaiae, its reproductive success depended directly on the presence of hummingbirds. This dependence on pollinators suggests that the conservation of F. itatiaiae may rely not only on measures targeting the species itself, but also on broader effort to protect the ecological interactions that sustain the local pollination network.